2004
DOI: 10.1097/01.prs.0000122217.16985.52
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Expression following Surgical Delay of Rat Transverse Rectus Abdominis Myocutaneous Flaps

Abstract: Partial transverse rectus abdominis myocutaneous (TRAM) flap loss in breast reconstruction can be a devastating complication for both patient and surgeon. Surgical delay of the TRAM flap has been shown to improve flap viability and has been advocated in "high-risk" patients seeking autogenous breast reconstruction. Despite extensive clinical evidence of the effectiveness of surgical delay of TRAM flaps, the mechanisms by which the delay phenomenon occurs remain poorly understood. To examine whether angiogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Angiogenic cytokines/growth factors such as basic fibroblast growth factor (bFGF) 55 and vascular endothelial growth factor (VEGF) are increased following delay and lead to new blood vessel growth. 56 Carroll et al 57 demonstrated increased muscle perfusion in a canine model of latissimus dorsi muscle delay using bFGF administration and increased latissimus dorsi muscle survival in a mouse model following PDGF administration.…”
Section: Neovascularizationmentioning
confidence: 99%
“…Angiogenic cytokines/growth factors such as basic fibroblast growth factor (bFGF) 55 and vascular endothelial growth factor (VEGF) are increased following delay and lead to new blood vessel growth. 56 Carroll et al 57 demonstrated increased muscle perfusion in a canine model of latissimus dorsi muscle delay using bFGF administration and increased latissimus dorsi muscle survival in a mouse model following PDGF administration.…”
Section: Neovascularizationmentioning
confidence: 99%
“…The surgical delay has been demonstrated to be a reliable procedure to improve pedicled flap's survival area, but so far, the optimal delay period is still a controversial issue, which may be 5 days, 7 days, 14 days, 21 days, or 8–10 days in the literature . Thus, how to determine the optimal delay time continues to be unknown in the clinical practice, because various surgical delay animal models and delay procedures may significantly influence the delay period of reaching the maximal delay effect . In addition, Holzbach et al and Myers and Cherry have demonstrated that the survival area of the postdelayed pedicled flaps is not proportional to the delayed duration.…”
mentioning
confidence: 99%
“…Cuando se utiliza un expansor tisular genera una cápsula altamente vascular que contribuye a la vascularidad del colgajo. Otro beneficio de dicho implante es que facilita la disección en el segundo procedimiento, a pesar de que el colgajo es más grueso y proporciona piel para un cierre directo del sitio donador [7][8][9][10].…”
Section: Discussionunclassified